Strategi Komunikasi Pemasaran Dalam Re-Branding UMKM Di Kelurahan Kepanjenkidul Kota Blitar - Bowo Santoso; Algi Ardiyansyah (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Basically, a marketing communication strategy involves selecting and using various effective communication channels to convey marketing messages to target markets. Re-branding is the process of changing the identity or image of a brand, product or company with the aim of updating, enhancing or changing consumer or public perceptions. Digital marketing is a marketing strategy implemented using digital platforms and the Internet to achieve business goals. The purpose of this community service is to develop and implement a marketing communication strategy for rebranding MSMEs in the Kepanjenkidul Village, Blitar City. The method is carried out through Forum Group Discussions and MSME observations regarding logo design, packaging design and digital marketing strategy assistance. The result of this community service is that MSMEs in the Kepanjenkidul Village area, Kepanjenkidul District, Blitar City feel very enthusiastic about carrying out the re-branding process and assisting digital marketing strategies.